Empreendedorismo feminino sustentável: um estudo sobre os modelos de negócios das munícipes de Barreirinha/AM - Andrade, Valderjane Gomes (Brasil, 2023)
The present study addresses female entrepreneurship in the context of the municipality of Barreirinha-AM. It aims to know the sustainable business models of women entrepreneurs, challenges and contributions to the economic development of the municipality of Barreirinha. For data collection, interviews, direct observation and content analysis were carried out, covering as subjects 10 female entrepreneurs from the municipality of Barreirinha, Amazonas. The results obtained show that despite underestimating the ability of women to make decisions, always comparing them with the opposite sex, it is clear that the entrepreneur has an even lower income, but with good expectations, as they demonstrate greater adaptability and openness to new knowledge, always ready for new challenges. Many are housewives and see in the retail trade a possibility of income to support their families. It can be seen that the growth of entrepreneurial activities is increasingly strengthened by gender balance. And the increase in the number of new ventures has been attributed to women who have a high rate of insertion in the business world.